THE INDUSTRIAL IMPACT OF OIL PRICE SHOCKS IN NIGERIA: (1970 – 2010) - Ojapinwa, Taiwo Victor; Ejumedia, Patrick Efe (European Scientific Journal, ESJ, 2012)
This paper examines the industrial impact of oil price shocks in Nigeria from 1970-2009, the econometric approaches adopted in the paper is the VAR impulse response. This study came out with empirical evidence that will help in understanding the impact of oil price shocks onaggregate industrial output in Nigeria while also considering other variables like Exchange rate, Inflation, unemployment and Money Supply. The study came to the conclusion that oil price, inflation and exchange rate has the potentials of causing significant changes in industrial output in Nigeria, while it was also revealed that industrial output was not significantly determined by money supply. This study therefore suggests that more policy attention should be given toproper management of the exchange rate and inflation.